Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1371/journal.pone.0188800
|View full text |Cite
|
Sign up to set email alerts
|

The sentinel tree nursery as an early warning system for pathway risk assessment: Fungal pathogens associated with Chinese woody plants commonly shipped to Europe

Abstract: Introduction of and invasion by alien plant pathogens represents the main cause of emerging infectious diseases affecting domesticated and wild plant species worldwide. The trade in living plants is the most common pathway of introduction. Many of the alien tree pathogens recently introduced into Europe were not previously included on any quarantine lists. To help determine the potential risk of pest introduction through trading of ornamental plants, a sentinel nursery was established in Beijing, China in 2008… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 44 publications
0
37
0
Order By: Relevance
“…Nonetheless, many newnon-native pests were previously unknown to be harmful, or even to science, and were therefore not regulated before they invaded. To address this issue, monitoring of sentinel plants in exporting countries has been proposed as a valuable tool to identify harmful organisms prior to their arrival [72,73,74]. Although several European projects (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless, many newnon-native pests were previously unknown to be harmful, or even to science, and were therefore not regulated before they invaded. To address this issue, monitoring of sentinel plants in exporting countries has been proposed as a valuable tool to identify harmful organisms prior to their arrival [72,73,74]. Although several European projects (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Sentinel planting, i.e., plants native to importing country planted in exporting countries that are inspected and analyzed at regular intervals for microbial pathogen detection, is the most promising tool (Eschen et al 2019). To this end, one could imagine associating other types of "biological" sensors that have already been the subject of promising studies, such as the sentinel plantations of European species exposed in an exotic environment (Vettraino et al 2015) or sentinel nurseries of non-native species found in their non-native environment of origin (Vettraino et al 2017). This type of sentinel also makes it possible to study the pathogenic potential and the phytosanitary risk caused by these taxa identified by their bar code sequence in air trapping (Aguayo et al 2018).…”
Section: Disease Preventionmentioning
confidence: 99%
“…Assuming that host-parasite co-evolution of native species might not result in obvious symptom expression, a host shift to a taxonomically similar plant species in the final location of the plant may give rise to novel host-parasite interactions. Therefore, diagnostic methods that can detect endophytic or latent pathogens must be employed (Vettraino et al 2017) in addition to standardized diagnostics for symptomatic tissue. Thus, sampling must be oriented to both symptomatic and nonsymptomatic material.…”
Section: Sentinel Nurseriesmentioning
confidence: 99%
“…as endophytes, latent infections) or on associated commodities (e.g. soil, wood packaging) (Roques et al 2015;Vettraino et al 2017). Thus, there is a need for better tools and strategies to improve early detection of potentially harmful species before they are introduced.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation